UJI ANGKA KUMAN DAN STABILITAS PRODUK SABUN CAIR FORMULASI HERBAL - DARINI KURNIAWATI (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2022)
Washing hands with soap can break the chain of the spread of Covid-19. People prefer to use liquid soap because it is more practical in packaging and using it. Therefore, we would like to further investigate the effectiveness of the herbal formulation liquid soap developed from previous studies. The purpose of this study was to determine the antibacterial stability and effectiveness of the herbal formulations of betel leaf, lime peel and bund in liquid soap products using the experimental True method, the hand washing group with herbal liquid soap, the control group, along with evaluation of pH, organoleptic, foam stability, moisture content. , free fatty acids and free alkalis. Liquid soap produced in liquid form, lemon smell and yellow color, foam 15-70 mm, pH 10, water content 52%, free fatty acids 0.05%, free alkali 0.091%. decrease in germ numbers by 90.5% and strengthened by bivariate analysis using Paired T test obtained a significance value of 0.0001 (<0.05). It can be concluded that the herbal liquid soap of betel leaf, lime peel and bundung plant complies with the required SNI standard for liquid soap and is effective in reducing the number of germs through hand washing activities. ABSTRAKMencuci tangan dengan sabun bisa memutus mata rantai penyebaran Covid-19. Masyarakat lebih senang menggunakan sabun cair karena lebih praktis kemasan dan penggunaannya. Oleh karena itu, kami ingin meneliti lebih lanjut efektifitas sabun cair formulasi herbal pengembangan dari penelitian sebelumnya. Tujuan peneliatian ini untuk mengetahui stabilitas dan efektivitas antibakteri formulasi herbal daun sirih, kulit jeruk nipis dan bundung dalam produk sabun cair dengan metode True eksperimental, kelompok mencuci tangan dengan sabun cair herbal, kelompok kontrol , beserta evaluasi ph, organoleptik, stabilitas busa, kadar air, asam lemak bebas dan alkali bebas. Sabun cair yang dihasilka bentuk cair, bau lemon dan warna kuning, busa 15 – 70 mm, pH 10, kadar air 52%, asam lemak bebas 0,05%, alkali bebas 0,091%. penurunan angka kuman sebesar 90,5% dan diperkuat dengan analisa bivariat menggunakan Paired T tes diperoleh nilai signifikansi 0,0001 (<0,05). Dapat disimpulkan sabun cair herbal daun sirih, kulit jeruk nipis dan tanaman bundung sesuai standar SNI sabun cair yang dipersyaratkan dan efektif menurunkan angka kuman melalui kegiatan cuci tangan.